Collaboration and Decolonisation: Revising a Course on Globalisation and Sustainable Development - Dansholm, Kerenina K.; Zeleke, Girum (Nordic Journal of Comparative and International Education (NJCIE), 2026)
This article explores collaboration between educators with complementary yet distinct relationships to racial capitalism and its role in pedagogical disruption of Nordic exceptionalism in sustainability education. The discussion is specifically situated within Norwegian higher education, where denaturalising 'imagined sameness' (likhet) requires tailored pedagogical strategies. Through counter-storytelling and collaborative autoethnographic reflection on our ‘tinkerings’ with the curricula of the jointly taught course ‘Globalisation and sustainable development’, we tell a story of our pedagogical strategies and the affective labour needed in sustained decolonial collaboration within predominantly white institutional spaces. Our reflection indicates that strategic collaboration has the potential to strengthen resistance to systems of oppression. Secondly, incremental ‘tinkering’ may be more effective in the long term than a dramatic curricular overhaul. And finally, context matters. Decolonisation of education must be a pluriversal effort – specific to the situatedness of the educational environment.